Emergency Department Admissions of Alcohol and Substance Use Disorders: A Two-Year Comparison from a University Hospital in Türkiye - Sungur, Ibrahim; Tugrul, Gulser Karakoc; Haznedaroglu, Damla Isman; Tuncel, Ozlem Kuman (Addicta: The Turkish Journal on Addictions, 2025)
Alcohol and substance use disorders present a growing public health challenge and are a significant cause of emergency department consultations. This study aims to compare the prevalence and clinical features of alcohol and substance use disorders–related emergency department admissions in 2 distinct years, 2018 (pre-pandemic) and 2023 (post-pandemic), at Ege University Medical Faculty Hospital in Türkiye. A retrospective cross-sectional analysis was conducted using psychiatric consultation data from the emergency department in 2018 and 2023. A total of 3189 adult patients who received psychiatric evaluation were included. Demographic and clinical data were extracted from electronic health records. Alcohol and substance use disorder diagnoses were made based on the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria. Alcohol and substance use disorders–related emergency department consultations increased from 19.8% in 2018 to 28.0% in 2023 (p < .001). The prevalence of substance use disorder rose from 14.5% to 17.7% (p = .014), while alcohol use disorder nearly doubled from 7.4% to 16.1% (p < .001). Among females, substance use disorder increased from 5.8% to 9.8% (p = .003), and alcohol use disorder tripled from 2.6% to 8.7% (p < .001). Comorbid alcohol use disorder and substance use disorder also showed a significant rise (2.1%–5.7%, p < .001). Alcohol use disorder–related hospitalizations increased from 4.5% to 12.6% (p = .01). Suicide attempts and violent behavior remained leading reasons for psychiatric consultation. The findings reveal a significant rise in alcohol and substance use disorders–related emergency department admissions, particularly among females. The increase in psychiatric crises such as violence and suicide attempts highlights the need for gender-sensitive prevention strategies and better training for emergency department staff to manage alcohol and substance use disorder–related emergencies.
Keywords: Addiction; alcohol use disorder; COVID-19; emergency department; substance use disorder